Immoral Daughters and Innocent Patriarchs. Gender and Romani Ethnicity in State Socialist Romania. Two cases studies - Andricioaei, Catalina (Romano džaniben, 2025)
This article explores how gender and Romani ethnicity intersected within the patriarchal structures of Romanian state socialism through two case studies separated by three decades. The first concerns a 14-year-old Romani girl institutionalized as a "juvenile delinquent" after reporting sexual abuse by her foster father in 1951. The second examines a woman who, in 1981, denounced her violent Romani husband to the Securitate for political crimes. Both cases reveal how class, age, and gender shaped institutional decisions in opposite ways: the girl’s "immorality" was racialized and punished, while the man’s violence was domesticated and forgiven. By reading denunciations, social reports, and character assessments as gendered bureaucratic practices, the article explores how socialist institutions perpetuated patriarchal and racial hierarchies under the guise of moral and social reform.